Formative Assessment Evaluating Formative Assessment in the Implementation of the Merdeka Curriculum - Fajar Imam Murifqi; Issy Yuliasri (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Formative assessment plays a critical role in supporting student learning by providing continuous feedback throughout the instructional process. However, many teachers have yet to implement formative assessment effectively, particularly in English language instruction under the Emancipated (Merdeka) Curriculum in Indonesia. This qualitative study investigates the implementation of formative assessment in an English class at SMP Daarul Qur’an Ungaran, a junior high school located in West Ungaran District. Data were collected through preliminary observations, classroom observations, interviews, and document analysis involving one English teacher and 28 eighth-grade students. Findings indicate that the teacher partially implements formative assessment strategies, including quizzes, oral questioning, and student reflections. However, certain aspects such as grammar and pronunciation assessments were found to be underutilized. Students generally responded positively to the feedback they received, though some formative techniques were inconsistently applied. The study highlights both the potential and the challenges of implementing formative assessment under the Emancipated Curriculum. It offers practical insights for educators and policymakers on how to improve assessment literacy and better integrate formative strategies into classroom practices to support student learning outcomes.